2016
DOI: 10.1007/s00464-016-5016-5
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of laparoscopic management of incarcerated obturator hernia

Abstract: In this study, laparoscopic technique was associated with a reduced duration of hospital stay and fewer complications. In addition to being a safe and minimally invasive strategy, it allowed for simultaneous diagnosis and treatment of occult hernias during the same procedure. The approach may be a better option for the treatment of incarcerated OH and occult hernias in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 18 publications
5
23
1
7
Order By: Relevance
“…Recent reports have revealed that a laparoscopic approach is safe and feasible for OH . In comparison to laparotomy, the laparoscopic approach for treating a small bowel obstruction is associated with a quicker recovery of gastrointestinal function, a shorter length of hospitalization, and fewer postoperative complications .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have revealed that a laparoscopic approach is safe and feasible for OH . In comparison to laparotomy, the laparoscopic approach for treating a small bowel obstruction is associated with a quicker recovery of gastrointestinal function, a shorter length of hospitalization, and fewer postoperative complications .…”
Section: Discussionmentioning
confidence: 99%
“…The incarcerated hernia can be laparoscopically reduced through gentle traction or water pressure, as well as with laparotomy . Moreover, other hernias on the contralateral side can be explored using a laparoscopic approach; a study reported that contralateral OH was found in 60% of patients with OH .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OH, accounts for 0.07-1.4% of all abdominal hernias. It has been known as a disease of elderly and skinny women (8)(9)(10)(11). It occurs more frequently in the right side (2,5,10).…”
Section: Introductionmentioning
confidence: 99%
“…It was first described in 1724 by Arnould de Ronsil (5,8). Low body mass index (BMI) and multiparity can be named among predisposing factors (1,9). Symptoms and physical examination findings are not specific.…”
Section: Introductionmentioning
confidence: 99%